mTORC1 regulates autophagosomal components recycling through SNX16 phosphorylation - Huilin Que; Fengping Liu; Yang Chen; Wenmin Tian; Shuaixin Gao; Catherine C. L. Wong; Yan Li; Shixuan Wang; Xianbin Meng; Yueguang Rong (Proceedings of the National Academy of Sciences, 2025)
During autophagy, the contents enclosed within autophagosomes are degraded, while the outer membrane components are recycled from autolysosomes by the recycler complex through the recently discovered autophagosomal components recycling (ACR) process. This recycling is essential for maintaining autophagic activity. However, the molecular machinery and upstream regulatory mechanisms driving this recycling process remain poorly understood. Here, we identify SNX16 as a key component of the recycler complex, which localizes to autolysosomes and is required for ACR. SNX16 functions in ACR by regulating recycler complex formation, facilitating cargo recognition, and mediating the connection between STX17–SNX4–SNX5 and dynein–dynactin complexes. In addition, SNX16–cargo interactions are regulated by two ACR-related small GTPases, Rab32 and Rab38. Importantly, mTORC1 phosphorylates SNX16 to regulate ACR by inhibiting its interactions with STX17 and other recycler components, thus preventing recycler complex formation. Taken together, our findings identify SNX16 as a recycler component and establish a link between mTORC1 and ACR.